(untitled) (International Journal of Engineering and Computer Science, 2016)
Block-based coding is used extensively both in image and video coding systems. Image coding systems that divide an image into sub-images have problems in very low bit rate applications. In low bit rate applications, this scheme gives rise to “blocking artifacts” that arise due to image segmentation which severely reduce the visual quality of an image or video. Reducing blocking artifacts is essential to render the compressed visual data acceptable to the viewer. Various deblocking methods have been proposed in the literature to reduce blocking artifacts. Many of these methods are based on the post-processing at the encoding side. In the presentresearch paper various deblocking methods applied in the frequency domain are discussed.